(untitled) - Asnawi, Rustam; Wan Ahmad, Wan Fatimah; A. Rambli, Dayang R. (2010)

(untitled)
In the future, utilization of dual display tends to be more popular. Optimizing the use of this feature, and designing a specific control panel user interface (UI), provide a possibility to develop an application that is able to unify the behavior of PC based multimedia player and presentation system. Since the view of the control panel and its output display occupied a different monitor, it is possible to create a single-compact control panel UI. Each multimedia element (video, image, slide, animation) have a particular controller and to be integrated in one window. This paper presents the Integrated Multimedia Player (IM-Player) an application that has been developed based on channel controller model and exploits the dual-display feature. We examined that the IM-Player has inherent double functions i.e. as a multimedia player and a presentation system simultaneously. Lastly, the IMPlayer enable to unify the behavior of multimedia player and presentation system in single application